Rancangan Aplikasi Renovasi Spesifikasi Ruangan Berbasis Web - Luthfiyah Nailah Nailah (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2021)
With the impact of this pandemic, all people are advised to be able to work, study and carry out activities from home. With the tchnology of an application that can help users choose the desired design and material without having to go to a building shop or juast consult face to face with renovator services. The system to be built will be designed in this application which is inteded to help customers and renovator services by simply filling in the options on a website. While the research methodology used in this research is object – oriented method. And the system development method used is the RAD method. Through the development of this system, it is hoped that the registration of renovations can be made faster and easier. Keywords: technological development, renovation, RAD methods.